Pengaruh Religiusitas, Pengetahuan dan Budaya Terhadap Minat Menabung pada Perbankan Syariah - Hilya Nur Syahidah; Banu Witono (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to examine the influence of religiosity, knowledge, and culture on saving interest in Islamic banking among students in Surakarta in 2024. The research uses a quantitative approach with a causal model, utilizing both primary and secondary data. The sample was selected using convenience sampling, and data were collected through questionnaires using a Likert scale. The findings indicate that religiosity and knowledge significantly influence saving interest, while culture has no significant effect. This study also faces limitations in normality testing, which can be addressed using the Monte Carlo method. This research contributes to understanding the factors affecting saving interest in Islamic banking.